2021
DOI: 10.9745/ghsp-d-20-00377
|View full text |Cite
|
Sign up to set email alerts
|

Galvanizing Action on Primary Health Care: Analyzing Bottlenecks and Strategies to Strengthen Community Health Systems in West and Central Africa

Abstract: Challenges with health financing, essential medical products and technology, and community ownership and partnerships emerged as the severe or very severe health system bottlenecks that hampered the strengthening of community health systems, irrespective of mortality context. n Country-led progress is possible. Potential strategies to overcome bottlenecks include increasing domestic allocation and leveraging innovative funding mechanisms for primary health care (PHC), integrating supply chain systems, and stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…In principle, a number of methods could be used to assess bottlenecks, such as highly structured surveys linked to administrative data at different levels of a delivery system ( 48 , 49 ), rapid assessments within a smaller number of units within the system ( 50 ), key informant interviews, and participatory workshops ( 51 ). These vary widely in terms of the time, resources, and technical expertise involved, as well as the robustness of the findings and additional benefits each may bring.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, a number of methods could be used to assess bottlenecks, such as highly structured surveys linked to administrative data at different levels of a delivery system ( 48 , 49 ), rapid assessments within a smaller number of units within the system ( 50 ), key informant interviews, and participatory workshops ( 51 ). These vary widely in terms of the time, resources, and technical expertise involved, as well as the robustness of the findings and additional benefits each may bring.…”
Section: Resultsmentioning
confidence: 99%
“…We estimate the cost-savings from the planned rightsizing and retargeting of the CHW workforce to be approximately US$3.8 million annually (40% of the current annual cost of US$9.5 million). 23 Cost-savings could be re-directed towards professionalising the CHW workforce and strengthening the health system and community enablers needed to optimise CHW performance, 1 2 9 which have been well described to have major shortfalls in Sierra Leone [46][47][48] and most national CHW programmes. 14 49-52 Second, our analysis highlighted an important gender disparity in CHW deployment (35% of CHWs were female and 65% were male).…”
Section: Implications For Policymentioning
confidence: 99%
“…Multiple articles describe the results of developing assessment tools that support reform of community health systems and improve functional population coverage. Simen-Kapeu et al conducted a bottleneck analysis of processes to strengthen and expand community health systems and strategies in 22 West and Central African countries 15 ; the analysis identified gaps in community health financing, lack of equipment and supplies, and limited community ownership. Morrow et al used the CHW Coverage and Capacity (C3) Tool to identify the required number of CHWs and their time allocation in Rwanda and Zanzibar, describing the importance of optimizing CHW investments by understanding the context and existing opportunities to engage with decision makers and stakeholders.…”
Section: Coverage Of Populationsmentioning
confidence: 99%
“…20 Consistent with that accelerating shift, financing is described as a critical bottleneck to achieving maturity and scale in several articles. 15,17,18,21 Saint-Firmin et al analyze the distribution of reported expenditure, efficiency, and geospatial mapping in Mali to inform decision makers in transitioning to a domestically funded CHW program. 22 They demonstrate where efficiencies could be found and targeted geographically to reach underserved communities.…”
Section: Community Health Financingmentioning
confidence: 99%
See 1 more Smart Citation